PERSISTENCE OF CRYSTAL-FORMING INSECTICIDE BACTERIA IN TYPICAL CHERNOZEM PLANTED WITH CABBAGE (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
It has been revealed that bacterial insecticides of BT species, isolated by us from dead caterpillars of fruit moth and winter geometrid, after introduction into typical chernozem planted with cabbage are being preserved in the given environment during 4–5 months and maintain intrinsic for mother strain ability to synthesize spores and crystals, as well as to show high biological effectiveness against caterpillars of diamond-back moth.
Keywords: bacterial insecticides; fruit moth; chernozem; cabbage; high biological effectiveness